Multilevel analysis of individual and community level factors associated with the application of cow dung and oil on the umbilical cord stump in Ethiopia - Dessie, Anteneh Mengist; Geremew, Habtamu; Feleke, Sefineh Fenta; Anley, Denekew Tenaw; Mruts, Kalayu Brhane; Yenew, Chalachew; Bantie, Berihun; Misganaw, Natnael Moges; Kerebeh, Gashaw; Gebeyehu, Asaye Alamneh; Asnakew, Desalegn Tesfa; Anteneh, Rahel Mulatie (Frontiers in Pediatrics, 2022)
Background: Hygienic umbilical cord care is one of the essential interventions advocated to reduce neonatal mortality. However, traditional cord care measures-applying cow dung and oil-that have harmful health consequences are commonly practiced in Ethiopia. Hence, in this study, it was planned to analyze individual and community-level factors associated with the application of cow dung and oil on the umbilical cord stump in Ethiopia. Methods: Data from the 2016 Ethiopian demographic and health survey were used to identify individual and community level factors associated with women’s practice of applying cow dung and oil on the umbilical cord stump of their neonate. Taking into account for the hierarchical structure of the data; multilevel binary logistic regression analysis has been employed to a nationally representative weighted sample of 7,168 women. Results: In Ethiopia, 780 (10.88%) with 95% CI (10.18-11.62) women apply oil and/or cow dung on the umbilical cord stamp of their neonate. Age increase by one year [AOR=0.97; 95% CI (0.94-0.99)] and giving birth in a health facility [AOR=0.61; 95% CI (0.42-0.89)] were individual-level variables associated with women’s practice of applying cow dung and oil on the umbilical cord stump of their neonate. Whereas, rural residence [AOR=2.54; 95% CI (1.28-5.06)] was the predictor at the community level. Conclusion: This nationwide study revealed that a significant number of mothers in Ethiopia still apply cow dung and/or oil on the umbilical cord stamp of their neonates. Both the individual and community level characteristics: maternal age, place of delivery, and residence were found to have significant inﬂuence on the practice of applying cow dung and/or oil on the umbilical cord stump in Ethiopia. Thus, to reduce neonatal mortality due to avoidable umbilical cord infections, clean cord care practice strategies should be designed by considering these factors.